Integrative Observations and Assessments - Nakano, Shin-ichi; Yahara, Tetsukazu; Nakashizuka, Tohru (Asia-Pacific Biodiversity Observation Network,, 2014)
This volume focuses on new trends in monitoring biodiversity in the Asia-Pacific region, one of the most rapidly changing areas in the world. It provides reviews of the challenges in studying the spatial variability of biodiversity across various ecosystems. This book also describes newly developed concepts and methods for biodiversity observation including ubiquitous genotyping, systematic conservation, monitoring of the functions and services of ecosystems, and biodiversity informatics. These contributions will lead to establishing integrative observations and assessments of biodiversity, essential for reporting the current status and for the effective conservation and sustainable use of biodiversity. This work will interest biodiversity researchers not only in the Asia-Pacific region, but also across the entire globe.